Greenwashing and financial performance in public health firms: the mechanism of organizational legitimacy erosion - Liang, Yaru; Gao, Xiang (Frontiers in Public Health, 2025)
IntroductionAmid China’s pursuit of its “dual carbon” objectives and the escalating emphasis on Environmental, Social, and Governance (ESG) disclosure, corporate environmental responsibility has emerged as a critical regulatory and market concern. However, mounting institutional and stakeholder pressures have incentivized some firms to engage in greenwashing—strategically overstating or misrepresenting their environmental commitments—to sustain legitimacy and competitive positioning.MethodsThis study empirically investigates the impact of greenwashing on corporate financial performance using panel data from 157 publicly listed Chinese public health firms between 2020 and 2022. A mediation model is utilized to identify the mechanism role of organizational legitimacy in affecting the relationship between greenwashing and corporate financial performance.ResultsThe findings reveal that greenwashing significantly undermines organizational legitimacy, which, in turn, leads to negative financial repercussions. Firms that overstate their environmental commitments experience diminished stakeholder trust, regulatory scrutiny, and reputational damage, ultimately eroding their financial performance.DiscussionBy analyzing the indirect pathways through which greenwashing influences firm performance, this research advances theoretical discourse on corporate environmental accountability and legitimacy-based performance dynamics. Furthermore, the study offers actionable insights for public health enterprises, emphasizing the necessity of transparent and verifiable environmental communication to mitigate reputational risks and ensure sustainable financial outcomes. Additionally, it provides empirical evidence to inform policymakers in refining regulatory frameworks that enhance transparency in environmental reporting and foster substantive sustainability practices.